2010
DOI: 10.1271/bbb.100337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Solvents on the Reverse Transcription Reaction Catalyzed by Reverse Transcriptases from Avian Myeloblastosis Virus and Moloney Murine Leukemia Virus

Abstract: The use of certain organic chemicals has been found to improve yields and specificity in PCR. In this study, we examined the effects of dimethyl sulfoxide (DMSO), formamide, and glycerol on the reverse transcription reaction catalyzed by reverse transcriptases (RTs) from avian myeloblastosis virus (AMV) and Moloney murine leukemia virus (MMLV). At 42 C, DMSO at 24% v/v and formamide at 12-14% inhibited the cDNA synthesis reaction, but DMSO at 12% and formamide at 6-8% improved the efficiency of the cDNA synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The activity of the a-subunit to incorporate dTTP into poly(rA)-p(dT) 15 was performed as described previously (Yasukawa et al 2010b). Briefly, poly(rA)-p(dT) 15 was prepared from p(dT) 15 (Life Technologies Japan Ltd) and poly(rA) (GE Healthcare, Buckinghamshire, UK).…”
Section: Measurement Of Amv Rt A-subunit Activity To Incorporate Dttpmentioning
confidence: 99%
“…The activity of the a-subunit to incorporate dTTP into poly(rA)-p(dT) 15 was performed as described previously (Yasukawa et al 2010b). Briefly, poly(rA)-p(dT) 15 was prepared from p(dT) 15 (Life Technologies Japan Ltd) and poly(rA) (GE Healthcare, Buckinghamshire, UK).…”
Section: Measurement Of Amv Rt A-subunit Activity To Incorporate Dttpmentioning
confidence: 99%
“…2(B) shows the specific activities of the reverse transcription reaction for WT and all the single variants. The reaction was carried out in 10 mM Tris-HCl buffer (pH 8.3) containing 50 mM KCl, 2 mM dithiothreitol (DTT), 5 mM MgCl 2 , 12.5 μM poly(rA)-p (dT) 15 15 . The RT concentration was determined with Protein Assay CBB Solution (Nacalai Tesque, Kyoto, Japan) with bovine serum albumin (Nacalai Tesque) as standard.…”
mentioning
confidence: 99%
“…Regarding this, we have found that glycerol inhibited the inactivation of MMLV RT during incubation at 43°C. 15) Glycerol is an osmolyte that reduces the water activity of the solution. It stabilizes proteins and folds denatured proteins correctly.…”
mentioning
confidence: 99%
See 2 more Smart Citations